Attention, consciousness, and inattentional blindness. - Wentzell, Alexander (Synthese, 2025)
This paper examines the connection between two distinct mental phenomena: attention and phenomenal consciousness. I identify two types of views. Equivalency views maintain that attention is both necessary and sufficient for phenomenal consciousness. Dissociationist views deny this. This paper presents a novel argument for dissociationism, by way of an empirical phenomenon called "inattentional blindness." Inattentional blindness occurs when subjects engaged in an attention-demanding task fail to see an otherwise visible but task-irrelevant stimulus. Dialectically, IB is unanimously cited by proponents of equivalency views as providing empirical support for their claims. I argue this thinking is backward: short of evincing equivalency views, inattentional blindness experiments create a dilemma. Resolved in one way, this dilemma falsifies the sufficiency claim. Resolved in the other, it falsifies the necessity claim. Thus, short of supporting the view, IB shows equivalency views are false. I close by considering how this result also limits which dissociationist view enjoys empirical support as well.